Downregulation of type III interferons in patients with severe COVID‐19. Issue 7 (13th April 2021) - Fukuda, Yosuke; Homma, Tetsuya; Inoue, Hideki; Onitsuka, Chisato; Ikeda, Hitoshi; Goto, Yuiko; Sato, Yoko; Kimura, Tomoyuki; Hirai, Kuniaki; Ohta, Shin; Yamamoto, Mayumi; Kusumoto, Sojiro; et al.
Abstract: Coronavirus disease 2019 (COVID‐19) is globally rampant, and to curb the growing burden of this disease, in‐depth knowledge about its pathophysiology is needed. This was an observational study conducted at a single center to investigate serum cytokine and chemokine levels of COVID‐19 patients, based on disease severity. We included 72 consecutive COVID‐19 patients admitted to our hospital from March 21 to August 31, 2020. Patients were divided into Mild‐Moderate I (mild) and Moderate II‐Severe (severe) groups based on the COVID‐19 severity classification developed by the Ministry of Health, Labor and Welfare (MHLW) of Japan. We compared the patient characteristics as well as the serum cytokine and chemokine levels on the day of admission between the two groups. Our findings indicated that the severe group had significantly higher levels of serum fibrinogen, d ‐dimer, lactate dehydrogenase, C‐reactive protein, ferritin, Krebs von den Lungen‐6, surfactant protein (SP)‐D, and SP‐A than the mild group. Strikingly, the levels of interleukin (IL)‐28A/interferon (IFN)‐λ2 were significantly lower in the severe group than in the mild group. We believe that reduced levels of type III interferons (IFN‐λs) and alterations in the levels of other cytokines and chemokines may impact the severity of the disease.